Meningkatkan Hasil Belajar IPS Tema Bumiku Menggunakan Model Pembelajaran Berbasis Masalah melalui Whatsapp Grup di Masa Pandemi Covid-19 pada Siswa Kelas VI SDN 1 Penengahan Bandar Lampung - Pebrinda, Pebrinda (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this classroom action research is to improve social studies learning outcomes for grade VI.A students of SDN 1 Penengahan, Kedaton District, Bandar Lampung City, Semester 2 of the 2019/2020 academic year. The form of this research is classroom action research which consists of 2 cycles, each cycle is carried out three times face-to-face meetings with the research subjects of class VI.A SDN 1 Penengahan students, totaling 33 students. Based on the results of the study, it can be concluded that the application of a problem-based learning model (PBL) assisted by Whatsapp Groups can improve social studies learning outcomes for students of class VI.A SDN 1 Penengahan, Kedaton District, Bandar Lampung City.